Carrier status of Acinetobacter among healthcare personnel and prevalence of the same in the environment - Dr. Kavita Nimboor; Dr. Shubha. D. S.; Dr. Sudhindra. KS; Dr. Sumanta A; Dr. Jagadevi (Tropical Journal of Pathology and Microbiology, 2018)
Background: Acinetobacter baumanii is an increasingly troublesome nosocomial pathogen, often with multidrug and multi resistant strains, mainly in intensive care units (ICUs), being responsible for different types of nosocomial infections.Objectives: The objective was to determine prevalence of carriers of Acinetobacter Spp. and predisposing risk factors among healthcare workers (HCWs) in ICUs and their role as source in nosocomial infection.Materials and Methods: Specimens from nose, throat, axilla and hands of all HCWs (55 (40 staff nurses, 15 attenders)) from ICUs and 30 HCWs from general wards were collected and processed by standard laboratory procedures.Results: Prevalence of A. baumanii carriers was 18.18%. Higher carrier rate was observed in male than female HCWs (12.72% Vs 5.5%). carrier rate was 22.2% and 18.75% in SICU and PICU respectively with none from general wards. Carrier rate was 7.3% at axilla and hands.Conclusion: Colonization of hospitalized patients play an important role in subsequent colonization of hands of hospital staff during trivial contacts, there by contributing to the spread and persistence of outbreaks.